Gelatin-polysaccharide based materials: A review of processing and properties - Asiyanbi, T. T.; Bio-Sawe, W.; Idris, Munirat Abolore; Hammed, Ademola Monsur (Universiti Putra Malaysia, 2017)
The advent of green technology has flourished biomolecule applications in medical, pharmaceutical and food products. Unlike synthetic materials, gelatin-polysaccharide matrixes are generally recognized as safe (GRAS). Gelatin-polysaccharide complexes are currently being utilized for the development of nano- and micro-particles, hydrogel, aerogel and films. Gelatin-polysaccharide based materials have offered improved characteristics depending on the type and concentration of polysaccharide and crosslinking agent. Gelatin-polysaccharide based materials function as bioactive compounds entrapment and encapsulation and anti-bacteria. This review provides concise information on the theory and technological applications of gelatin-polysaccharides based materials.